THE EFFECT OF EDUCATIONAL MODELS ON DEVELOPING SOME PHYSICAL AND SKILL ABILITIES IN FOOTBALL FOR DEAF AND DUMB PLAYERS - Maytham Mohsin Habeeb; Munadhil Adil Kiasm (Proximus Journal Publishing, 2025)
The research sought to create exercises utilising educational models and to assess their effect on the enhancement of specific physical talents and skills. In theoretical studies, the researchers addressed educational models and their significance, referencing a prior study, and employed the experimental approach utilising a fundamental design known as the design of two equivalent groups. The sample was divided into two groups of ten players each; the control group followed the standard curriculum, while the experimental group adhered to the same educational curriculum but utilised instructional models. Additionally, the use of suitable methods, instruments, and apparatus for research protocols and the selection of assessments for specific football talents under investigation. The researchers first administered pre-tests, subsequently implemented the educational models, and then conducted post-tests under identical conditions to the pre-tests. Following this, the research results were analysed using their statistical methods, leading to several conclusions. Notably, the group that engaged with the educational models exhibited a positive influence on the enhancement of certain physical abilities (speed and speed-related strength) and skills (passing, dribbling, shooting, and ball control). The standard curriculum positively influenced the enhancement of physical abilities. A key recommendation from the researchers is to utilise educational models within educational institutions to cultivate specific physical and skill competencies in football, as well as to generalise these models for teaching deaf and mute players football skills and improving their performance.
Keywords: educational models; physical; football; players